PENGARUH PUPUK KOMPOS TERHADAP PERTAMBAHAN TINGGI ANAKAN JENGKOL (Pithecolobium jiringa) PASCA TIGA BULAN PENYAPIHAN - M. Fadjeri; Hasanudin Hasanudin; Dwinita Aquastini; Emi Malaysia; M. Masrudy; Noorhamsyah (Politeknik Pertanian Negeri Samarinda, 2023)
The aim of this study was to determine the effect of composting on the height increase of Jengkol (Pithecolobium jiringa) puppies after three months of weaning at the Samarinda State Agricultural Polytechnic Nursery. This study used a completely randomized design, with 4 types of treatment on weaning media and 10 replications. The treatments were N0 (pure sub soil), N1 (75% sub soil + 25% compost), N2 (50% sub soil + 50% compost) and N3 (25% sub soil + 75% compost). Based on the results of the study, it was shown that the height of jengkol (Pithecolobium jiringa) seedlings was treated with different growth media, namely planting media (subsoil) without compost (N0), planting media with a ratio of subsoil and compost compared to 75% : 25% (N1), planting media with a ratio of subsoil and compost 50% : 50% (N2) and planting media with a ratio between subsoil and compost 25% : 75% (N3). that all growing media gave a positive response to the height increase of jengkol (Pithecolobium jiringa) seedlings. Treatment N2 showed greater height gain, but based on the Least Significant Difference Test (LSD) at the 95% confidence level, treatments N1 and N2 were not significantly different.